HUBUNGAN KOMUNIKASI ANGGOTA KELOMPOK DENGAN KINERJA PETANI JAGUNG DI DESA AMESIU KECAMATAN PONDIDAHA KABUPATEN KONAWE - Sulastri, Anci; Wunawarsih, Ima Astuty; Lasinta, Megafirmawanti; Isnian, Sitti Nur (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The objective of this study is to ascertain the correlation between the efficacy of group communication and the performance of corn farmers in Amesiu Village, Pondidaha District, Konawe Regency. The research population consists of all corn farmer groups in Amesiu Village, with a total of 12 groups comprising 180 corn farmers. The sample size was determined using the Slovin formula with a margin of error of 10%, resulting in a sample of 64 respondents.  The data were collected through a combination of interviews, documentation, and surveys, with questionnaires serving as the primary instruments. The research variables of interest were group member communication and corn farmer performance. The research data was then subjected to quantitative analysis. This analysis method was carried out in two ways: descriptive analysis and Spearman's rank correlation analysis. The results indicated that the communication exhibited by the corn farmer group was classified within the "good" category, as evidenced by the indicators of solidarity, group intensity, communicative actions, and motivation. This observation reflected the farmers' capacity to establish productive interactions. The performance of farmer groups was also classified as good based on quality, quantity, timeliness, effectiveness, and independence. Additionally, a robust and substantial relationship was identified between group communication and performance, indicating that enhanced communication among group members is associated with elevated performance levels.